Pengaruh Perbedaan Jumlah Santan dan Lama Penyimpanan Beku Terhadap Viabilitas Lactobacillus acidophilus dalam Es Krim Nabati Probiotik - Widyastuti Effendi, Srianta, Netty Kusumawati, (Widya Mandala Surabaya Catholic University, 2007)
Ice cream is one of dairy-based frozen desserts which has a huge potency to be developed into a probiotic product. Cells viability is the main concern in formulation and processing of probiotic ice cream. Freezing and frozen storage are critical for cell viability. Recently, considerable interest has been shown in non-dairy ice cream which is suitable for vegetarians and people who are lactose intolerant. Usually, the non-dairy ice cream uses soymilk combined with coconut milk to increase fat and total solid. The objective of this research is to study the effect of coconut milk level (50 g/500 g and 160 g/500 g) and frozen storage time(0;7;14;21;and 28 days) on viability of Lactobacillus acidophilus in non-dairy probiotic ice cream. The coconut milk level of 50 g/500 g produced the non-dairy ice cream with total fat of 3.78% (mellofreeze), total solid of 25.37% and overrun of 8.26%, while its level of 50 g/500 g produced non-dairy ice cream with total fat of 9.52% (mellorine), total solid of 34.53% and overrun of 42.84%. The differences of coconut milk level and frozen storage times significantly affected the viability of Lactobacillus acidophilus. The coconut milk levesl of 50 g/500 g and 160 g/500 g produced ice cream with the cell viability of 10.22 log cfu/ml and 11.12 log cfu/ml, respectively. The Lactobacillus acidophilus viability decreased significantly after 7 days, but not for further storages. At the end of storage (28 days), the viable cells were 8 to 9 log cfu/ml, which complied with the probiotic prerequisite.